Safety of intrabiliary radiofrequency ablation in cases of residual and recurrent neoplasia after endoscopic papillectomy - Dahel, Yanis; Caillol, Fabrice; Ratone, Jean-Philippe; Zemmour, Christophe; Palen, Anais; Garnier, Jonathan; Ewald, Jacques; Turrini, Olivier; Hoibian, Solene; Giovannini, Marc (Endoscopy International Open, 2025)
Intrabiliary radiofrequency ablation (IB-RFA) is a therapeutic option for cases of positive margin or recurrence after endoscopic papillectomy (EP) for superficial neoplasia. We report our experience concerning safety and efficiency of IB-RFA.This was a single tertiary center retrospective study. All patients who underwent IB-RFA indicated for residual or recurrent neoplasia after EP were included. We assessed morbidity (<30 days) and late complications (>30 days). Secondary outcomes were clinical success and late recurrence (absence of recurrence at the papillectomy site 12 months after IB-RFA and recurrence beyond 12 months, respectively).Twenty-five patients were included and underwent IB-RFA for deep positive margins (20/25, 80%) or relapse (5/25, 20%) and 40 sessions were delivered. The morbidity rate was 8% (2/24) (1 pancreatitis, 1 bleeding). Acute pancreatitis was significantly more common in the absence of pancreatic stenting (0% vs. 22%, P=0.046). One patient for whom pancreatic stenting failed died from acute severe pancreatitis in the first month (mortality rate=4%). Late complications occurred in 12 of 24 patients (50%) concerning only biliary stricture, all of which were managed endoscopically without sequelae. The clinical success rate was 92% (22/24), and late recurrence occurred in two of 24 patients (8%).IB-RFA is relatively safe and efficient in cases of residual or recurrent neoplasia after EP and is an alternative to surgery in well-selected cases. Biliary stricture occurred frequently (50%) but could be managed endoscopically without sequelae in all cases. In cases of pancreatic stenting failure and because of the risk of severe and potentially lethal acute pancreatitis, IB-RFA should be postponed.
Keywords: Pancreatobiliary (ERCP/PTCD); ERC topics; Strictures; Endoscopy Upper GI Tract; RFA and ablative methods